PHYTOCHEMICAL ANALYSIS AND COMPARATIVE ANTIPARKINSON ACTIVITY OF FOUR SPECIES OF MUCUNA - M, Karunanithi; Raj C, David; P, Brindha; M, Jegadeesan; S, Kavimani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim was to study the antiparkinson activity in the seed extracts of four species of Mucuna. Methods: The hydroalcoholic extracts of seeds of four species of Mucuna were evaluated for antiparkinson activity of after a preliminary phytochemical study. The activity was measured in rats by indirectly measuring the decrease in malondialdehyde level, decrease in tongue protrusion frequency, and reduction in vacuous chewing movement after administering reserpine at the dose of 1 mg/kg. The dose levels of four species of Mucuna seed extract were kept at 100, 200, and 300 mg/Kg. Results: Extracts exhibited potent antiparkinson activity and achieved statistically significant p values compared with control group. The study corroborates and compares all four species of Mucuna. Conclusion: Among the extracts, the highest percentage of antiparkinson activity was recorded for Mucuna pruriens.